Modelling environmental benefits of silvoarable agroforestry in Europe - Palma, J.H.N. (2010)
Increased adoption of silvoarable agroforestry (SAF) systems in Europe, by integrating trees and arable crops on the same land, could offer a range of environmental benefits compared with conventional agricultural systems. Soil erosion, nitrogen leaching, carbon sequestration and landscape biodiversity were chosen as indicators to assess a stratified random sample of 19 landscape test sites in the Mediterranean and Atlantic regions of Europe. At each site, the effect of introducing agroforestry was examined at plot-scale by simulating the growth of one of five tree species (hybrid walnut Juglans spp., wild cherry Prunus avium L., poplar Populus spp., holm oak Quercus ilex L. subsp. ilex and stone pine Pinus pinea L.) at two tree densities (50 and 113 trees ha 1) in combination with up to five crops (wheat Triticum spp., sunflower Helianthus annuus L., oilseed rape Brassica napus L., grain maize and silage maize Zea mays L.). At landscape-scale, the effect of introducing agroforestry on 10 or 50% of the agricultural area, on either the best or worst quality land, was examined. Across the 19 landscape test sites, SAF had a positive impact on the four indicators with the strongest effects when introduced on the best quality land. The computer simulations showed that SAF could significantly reduce erosion by up to 65% when combined with contouring practices at medium (>0.5 and <3 t ha 1 a 1) and high (>3 t ha 1 a 1) erosion sites. Nitrogen leaching could be reduced by up to 28% in areas where leaching is currently estimated high (>100 kg N h 1 a 1), but this was dependent on tree density.With agroforestry, predicted mean carbon sequestration through immobilization in trees, over a 60-year period, ranged from 0.1 to 3.0 t C h 1 a 1 (5–179 t C h 1) depending on tree species and location. Landscape biodiversity was increased by introducing SAF by an average factor of 2.6. The implications of this potential for environmental benefits at European-scale are discussed.